2016
DOI: 10.5123/s1679-49742016000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da satisfação dos usuários dos Centros de Especialidades Odontológicas da macrorregião Sudeste de Minas Gerais, 2013

Abstract: he majority of patients were satisfied with the service provided; variables not analyzed in this study, including infrastructure, human resources and management, may have influenced the differences in patient satisfaction found between the different SDCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
1
8
2
1
Order By: Relevance
“…Regarding sex, most respondents are female, which alludes to the belief that self-care and care for others are values associated with femininity, linked to the lower labor force participation rate of women in our society 14 . However, satisfaction is strongly associated with men, which is consistent with the literature that shows services receiving more criticism from women, who are thus good informants for surveys 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sex, most respondents are female, which alludes to the belief that self-care and care for others are values associated with femininity, linked to the lower labor force participation rate of women in our society 14 . However, satisfaction is strongly associated with men, which is consistent with the literature that shows services receiving more criticism from women, who are thus good informants for surveys 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The results on QC Social Control and Financing demonstrate the low participation and listening of the users' needs, contrary to the understanding that the user should be seen as an important social actor of evaluations of programs and services, since his vision can modify health practices, making it most humane, welcoming and resolute. It is also worth noting that the evaluation from users is considered evaluation of the results of health interventions, with instruments validated for this purpose and developed studies [7,8]. In spite of financing problems, the difficulty of managing resources received and the insufficient investment of resources stand out.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of the main researches developed has shown advances such as: expansion of the offer, coverage and use of these services [2][3][4][5][6], as well as the degree of user satisfaction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…1 As such, service user dissatisfaction with health care is related to lower adherence to or interruption of treatment, less use of services and, consequently, poorer outcomes. [6][7][8][9][10][11][12] Lack of service users' views in the evaluation process leads to the result being biased by the views of service managers or health workers, 4 since technical evaluation is different to evaluation made by service users. 13,14 Blendon et al 13 found negative correlation between subjective evaluation by service users and the quality ranking for health systems estimated by the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%